Tapentadol exposures and poisonings in Australia. (2nd September 2022) - Chan, Betty S.; Mirabella, Jennifer; Allen, Katherine; Berling, Ingrid; Chiew, Angela L.; Isoardi, Katherine; Brown, Jared; Isbister, Geoffrey
Abstract: Introduction: Tapentadol is an atypical opioid with mu-receptor affinity and noradrenaline reuptake inhibition approved for use in Australia in 2011. However, data on tapentadol poisoning are scarce. Objectives: To investigate tapentadol poisonings and related deaths in Australia. Methods: We performed a retrospective review of tapentadol poisonings from New South Wales Poisons Information Centre (NSWPIC) and three toxicology units in Australia. The National Coronial Information System (NCIS) database was searched to determine the number of tapentadol-related deaths. Results: Between 2016 and 2020, 220 tapentadol calls were made to NSWPIC, with a 4.5-fold increase in tapentadol exposure calls. The median dose ingested was 575 mg (IQR: 300–1163 mg). Most overdoses included co-ingestions (75%), especially benzodiazepines (26%) and opioids (25%). From Jan 2016 to Dec 2021, 107 patients presented to the three toxicology units with tapentadol poisoning. The median dose ingested was 500 mg (IQR: 200–1400 mg). Most patients took co-ingestants (84%), including benzodiazepines (40%) and opioids (32%). Naloxone was administered in 39 patients (36%), 10 (9%) were intubated and the median length of stay was 18 h (IQR: 9–30). Thirty-five tapentadol-related deaths were recorded within NCIS between Jan 2015 and Oct 2021 with a median age of 51 years (IQR: 42–61 years). Conclusion: There are increasing tapentadol poisonings and deaths reported to the NSWPIC, three toxicology units, and NCIS in Australia. Most tapentadol poisonings were taken with benzodiazepines and/or other opioids.